GALL BLADDER ASCARIASIS: A RARE ENTITY - Akbar, Ismail; Zanib Javed,; Zaib, Zainab (Journal of Ayub Medical College Abbottabad, 2023)
Gall bladder ascariasis is a rare entity accounting for only 2.1% of biliary ascariasis features due to anatomical features of the cystic duct. It usually presents with vague abdominal features. Ultrasonography is the most sensitive and useful investigation for its diagnosis. We present a case of gall bladder ascariasis in an antenatal young female patient showing features of cholecystitis. She was diagnosed by ultrasonography and managed by laparoscopic cholecystectomy followed by oral anti-helminthic drugs. She made an uneventful recovery and is doing great in follow up visits.